2017
DOI: 10.21101/cejph.a5105
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Evaluation of Local Muscular Load while Typing on a Keyboard

Abstract: The results indicated that all probands in our study exceeded the valid hygienic limits for the total amount of the small repetitive movements of the hands and forearms and the total amount of the keyboard typing movements. Most of the probands in our study also exceeded the valid hygienic limit for the highest average time-weighted value of the percent maximum voluntary contraction (%MVC). This implies that the keystroke dynamics method has a great potential to increase the accuracy of evaluation of local mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The results of our study correspond to our expectations. They can be compared, for example, to a previous study on the evaluation of local muscle load during typing (11), where it has also been shown that the forces were above the limit, but in an average shift did not exceed the hygienic limit.…”
Section: S16mentioning
confidence: 99%
“…The results of our study correspond to our expectations. They can be compared, for example, to a previous study on the evaluation of local muscle load during typing (11), where it has also been shown that the forces were above the limit, but in an average shift did not exceed the hygienic limit.…”
Section: S16mentioning
confidence: 99%
“…Compared to existing finger strength training devices, the training method in this study explicitly targets the finger force www.ijacsa.thesai.org direction and coordination required in office scenarios. Previous research has shown evidence that standard keyboards can improve the fine motor skills of the fingers when typing [34,35] and their coordination [36]. This training device adjusts the critical resistance and provides interactive feedback to facilitate finger movements.…”
Section: Training Methodsmentioning
confidence: 99%